Significance and Management of Chickpea Wilt/root rot and Future Prospects in Ethiopia. A Review - Asrat Z (International Journal of Life Sciences, 2017)
Chickpea production and productivity in Ethiopia has recently declined and high potential yield gaps because of several abiotic and biotic factors. The average chickpea yield in Ethiopia is usually below 2 t/ha although its potential yield is more than 5 t/ha. It is resulted from susceptibility of chickpea landraces to heat stress, terminal drought, water-logging and poor cultural practices. One of the greatest biotic stress reducing potential yields in chickpea is chickpea wilt/root rot caused by Fusarium oxysporum f.sp. ciceris which is serious problem especially in the rain fed area. The diseases were more prevalent in most of North western and Central Ethiopia and high disease incidence was found on local than improved variety. Fusarium wilt is both seed and soil borne disease. In Ethiopia, about 30% yield loss of chickpea due to chickpea wilt has been reported. The wilt root rot caused yield loss of 50–80% in some farmers’ fields and sometimes even 100% loss on local variety. The fungus can survive in soil as means of chlamydospore and in chickpea debris. The pathogen only pathogenic to chickpea and another legume and weed species also serve as symptomless carrier. Spores can be moved short distance through rain splash, wind, water moving and farm machinery to surrounding plants and transported over large distance in infected seed in to new area. There was four race of pathogenic variability were well known in the country. Chickpea wilt/root rot controlled through use of resistant cultivar is most cost effective and practicable approach. The integrated management strategies like resistant cultivar, bed preparation, sowing time, soil-solirazation, bio-control, bio-fumigants and chemical treatments best approach to reduce the incidence of the wilt/root rot of chickpea and optimization of the yields. Therefore, the further studies of pathogen races, development of other management methods and verification of available methods need focus and encouragements on production of bio control agents as components of integrated disease management. In these paper, available management and epidemiology wilt/root rot disease were reviewed in chickpeas in Ethiopia.